Computer Model Analysis of Dynamic Performances of the Excitation Control System When the Load Angle Limiter Is Active - Joksimović, Dušan; Dragosavac, Jasna; Veinović, Slavko; Stojić, Đorđe; Marinković, Milan; Đorđević, Milan (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
A load angle limiter was implemented as an additional function in the existing excitation system to enable the operation of the synchronous generator in the entire P-Q diagram according to the recommendation of the manufacturer of the unit B2 synchronous generator in the "Nikola Tesla B" TPP. The analysis of dynamic performance presented in this paper consists of determining the time responses and frequency characteristics of the excitation control system when the load angle limiter is active, based on which the values of the dynamic performance indexes were obtained. In addition, the paper also provides a brief description of the implementation of the limiter, as well as a description of the computer models used in the analysis.